Pengaruh Harga, Lokasi, dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Counter Indo Cell Kudus - Irvan, Irvan Ardiansyah; Nathaniel, Nathaniel Igracio Leonaputra; Verdi, Verdi Indra Rizky; Krisna, Laurentius Krisna Adi Saputra (Kajian Ekonomi dan Bisnis, 2023)
This research will aim to analyze how much influence the independent variables, namely price, location and service quality have on the dependent variable of consumer satisfaction at the Indo Cell Kudus counter. This research uses quantitative methods. The data in this research was collected through a survey method using purposive sampling techniques. Questionnaires were distributed to 96 respondents who had made a purchase at the Indo Cell Kudus counter at least once. The data resulting from distributing the questionnaire will be processed using the SPSS software analysis tool. The selected results and analysis tests include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing via t test, F test, and analysis of the coefficient of determination (R2). From the research results and data analysis results, the following conclusion can be drawn: there is a positive but not significant influence of the price variable on consumer satisfaction at the Indo Cell Kudus counter. There is a positive and significant influence of location variables on consumer satisfaction at the Indo Cell Kudus counter. There is a positive and significant influence of the service quality variable on consumer satisfaction at the Indo Cell Kudus counter.   Keywords: Price, Location, Service Quality, Consumer Satisfaction